Improving livelihood in pastoral systems through an entrepreneurial ecosystem approach to sustainable sheep and goat production: tools for rapid assessment in pastoral systems - Ojango, Julie M.K.; Sila, Winfred; Mukalo, Irene; Okoth, Joshua; Lekimariki, Joshua; Nyanja, Belphine; Oyieng, Edward (CGIAR System Organization, 2024)
The Small Ruminant Tools for Rapid Assessment of Pastoral Systems (STRAPS) initiative supports sustainable sheep and goat production in pastoral systems by integrating traditional knowledge, modern breeding techniques and sustainable practices. Developed by the International Livestock Research Institute (ILRI), RECONCILE and the Baringo County Livestock Department, STRAPS provides four e-tools to assess three groups of actors in the value chain: pastoral communities, individual producers, service providers and market agents. Using the Open Data Kit platform, STRAPS generates actionable data to improve productivity, strengthen market links and address systemic challenges. By fostering an entrepreneurial ecosystem, the initiative enhances pastoralist livelihoods, boosts climate resilience and supports sustainable livestock systems in semi-arid regions.